“Context, Please?” The Effects of Appearance- and Health-Frames and Media Context on Body-Related Outcomes - Binder, Alice; Noetzel, Selina; Spielvogel, Ines; Matthes, Jörg (Frontiers in Public Health, 2021)
Promoting health-related behaviors such as eating healthy or doing sports seems important to counteract the rising obesity. In this regard, first studies suggest that appearance compared to health framing can lead to negative body-related outcomes in young women. This study aimed to extend these findings by investigating the role of context. Furthermore, as previous studies focused on young women only, we recruited a more diverse sample. This seems especially important as health campaigns focusing on healthy eating and sports should appeal to a more diverse population. This experimental study (N = 286) follows a 2 (appearance- vs. health-frame) x 2 (social media vs. magazine website) between-subjects design. Results revealed that exposure to appearance-focused framing led to less positive mood compared to health-focused framing. These effects were most prevalent for overweight and obese participants. Moreover, participants in the social media condition showed less body satisfaction and less positive mood compared to the magazine website condition independent of the frame. No other interaction effects occurred. Overall, health promoters should focus their campaigns on the health aspects of health-related behavior and very carefully consider its promotion on social media platforms. Also, they should keep in mind that not only the framing, but also the context might have effects on body-related outcomes.